Dietary intakes of elite 14- to 19-year-old English academy rugby players during a pre-season training period - Smith, D. R.; Jones, B.; Sutton, L.; King, R. F. G. J.; Duckworth, L. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Good nutrition is essential for the physical development of adolescent athletes, however data on dietary intakes of adolescent rugby players are lacking. This study quantified and evaluated dietary intake in 87 elite male English academy rugby league (RL) and rugby union (RU) players by age (under 16 (U16) and under 19 (U19) years old) and code (RL and RU). Relationships of intakes with body mass and composition (sum of 8 skinfolds) were also investigated. Using 4-day diet and physical activity diaries, dietary intake was compared with adolescent sports nutrition recommendations and the UK national food guide. Dietary intake did not differ by code, whereas U19s consumed greater energy (3366 ± 658 vs. 2995 ± 774 kcal·day-1), protein (207 ± 49 vs. 150 ± 53 g·day-1) and fluid (4221 ± 1323 vs. 3137 ± 1015 ml·day-1) than U16s. U19s consumed a better quality diet than U16s (greater intakes of fruit and vegetables; 4.4 ± 1.9 vs. 2.8 ± 1.5 servings·day-1; nondairy proteins; 3.9 ± 1.1 vs. 2.9 ± 1.1 servings·day-1) and less fats and sugars (2.0 ± 1. vs. 3.6 ± 2.1 servings·day-1). Protein intake vs. body mass was moderate (r = .46, p < .001), and other relationships were weak. The findings of this study suggest adolescent rugby players consume adequate dietary intakes in relation to current guidelines for energy, macronutrient and fluid intake. Players should improve the quality of their diet by replacing intakes from the fats and sugars food group with healthier choices, while maintaining current energy, and macronutrient intakes.